2023
DOI: 10.1111/jcmm.17747
|View full text |Cite
|
Sign up to set email alerts
|

Severity of the Omicron SARS‐CoV‐2 variant compared with the previous lineages: A systematic review

Abstract: The Omicron variant was first detected in October 2021, which evolved from the original SARS‐CoV‐2 strain and was found to possess many mutations. Immune evasion was one of the notable consequences of these mutations. Despite Omicron exhibiting increased transmissibility, the rates of hospitalizations and deaths among patients infected with this variant were substantially lower when compared to other strains. However, concluding that the Omicron variant is less severe than other variants of SARS‐CoV‐2 requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 105 publications
1
10
0
Order By: Relevance
“…Coronaviruses can cause psychopathological effects through two pathways: direct viral infection of the central nervous system or indirect effects via immune response [ 27 ]. Considering the relatively mild nature of the Omicron variant [ 28 ], there may have been a smaller biological inflammatory response, leading to a potentially reduced effect on depression and anxiety levels. This is consistent with a previous study conducted on SARS-CoV-2 infected inpatients, where patients with Omicron variant infection exhibited decreased depression and anxiety symptoms [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronaviruses can cause psychopathological effects through two pathways: direct viral infection of the central nervous system or indirect effects via immune response [ 27 ]. Considering the relatively mild nature of the Omicron variant [ 28 ], there may have been a smaller biological inflammatory response, leading to a potentially reduced effect on depression and anxiety levels. This is consistent with a previous study conducted on SARS-CoV-2 infected inpatients, where patients with Omicron variant infection exhibited decreased depression and anxiety symptoms [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients of the Omicron-dominant period were more likely to complain about coughing. A systematic review by Arabi et al concluded that the Omicron variant is less severe, with a related pandemic wave reporting lower rates of hospitalization, intensive care unit admissions, deaths, and patients needing oxygenation/ventilation [ 34 ]. Other studies performed in Poland complemented these findings, indicating that the Delta variant is associated with a more severe disease course and a higher risk of death relative to Omicron [ 3 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since most cells of the throat and nose lack this protein, Omicron invades them via endocytosis [ 51 ]. Consequently, despite the greater transmissibility of Omicron, it infects the upper respiratory tract, while other strains infect the lower respiratory tract, making Omicron less harmful to humans [ 34 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that patients infected with the Delta variant of the SARS-Cov-2 virus had more severe symptoms than the patients infected with the Omicron variant. 89 Vieillard-Baron et al, 19 for example, found that Omicron patients were 64% less likely to develop pneumonia than Delta patients. Ulloa et al 18 also determined that the risk of hospitalization amongst Omicron patients was reduced by 65% (compared to Delta patients), and the risk of admission to the ICU (intensive care unit) or death was reduced by 83% (compared to Delta patients).…”
Section: Discussionmentioning
confidence: 99%